2002
DOI: 10.1086/341612
|View full text |Cite
|
Sign up to set email alerts
|

Chromospherically Active Stars. XXI. The Giant, Single-lined Binaries HD 89546 and HD 113816

Abstract: We have obtained spectroscopy and photometry of the chromospherically active, single-lined spectroscopic binaries HD 89546 and HD 113816. HD 89546 has a circular orbit with a period of 21.3596 days. Its primary has a spectral type of G9 III and is somewhat metal-poor with [Fe/H] $ À0.5. HD 113816 has an orbit with a period of 23.6546 and a low eccentricity of 0.022. Its mass function is extremely small, 0.0007 M , consistent with a very low inclination. The primary is a slightly metal-poor K2 III. A decade or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 38 publications
1
50
1
Order By: Relevance
“…UX Ari also displays long-term variations in its mean brightness, suggesting cyclic behaviour. The RSM can reproduce such behaviour via the random appearance and decay of individual starspots without the need for a driving mechanism, as shown by the sample light curves generated by the RSM in Eaton et al (1996) and Fekel et al (2002).…”
Section: Spot Evolutionmentioning
confidence: 99%
“…UX Ari also displays long-term variations in its mean brightness, suggesting cyclic behaviour. The RSM can reproduce such behaviour via the random appearance and decay of individual starspots without the need for a driving mechanism, as shown by the sample light curves generated by the RSM in Eaton et al (1996) and Fekel et al (2002).…”
Section: Spot Evolutionmentioning
confidence: 99%
“…Therefore, our measured rotation periods from the individual seasons probably have true errors larger than the formal uncertainties in the period analysis. As discussed by Fekel et al (2002), the observed photometric periods in chromospherically active stars must be interpreted with care, since they can be affected by the growth and decay of individual spots at various longitudes, as well as the formation of new and decay of old clumps of spots by differential rotation, so that the photometric period at any epoch may not correspond precisely to the rotation period of any stellar latitude. It appears, therefore, that our photometry does not successfully reveal any differential rotation in HD 37824.…”
Section: Photometric Analysismentioning
confidence: 99%
“…V2253 Oph is a short-period asynchronously-rotating star in a binary with an orbital period 15 times longer than the stellar rotation period. Its orbit is only slightly eccentric, if at all, because zero eccentricity is within 3σ of the value given by Fekel et al (2002). Thus, the period difference could not be due to pseudosynchronization.…”
Section: Introductionmentioning
confidence: 86%
“…Its inclination of the rotational axis is coplanar to the orbit, which itself is highly eccentric (Griffin 1988). The third system, IS Vir, is a synchronized giant in a marginally eccentric orbit (Fekel et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation